India : Financial Sector Assessment Program: Insurance Sector Regulation and Supervision-Technical Note. (IMF Staff Country Reports; Country Report, 2018)
This Technical Note provides an assessment of the recent development of regulation and supervision of the Indian insurance sector. The sector has continued to grow in scale and diversity, surmounting the adverse impact of the global financial crisis, although penetration remains relatively low. Public sector insurers continue to command a majority of the market and life insurance predominates, with about 75 percent of total premiums. Non-life insurance is dominated by motor insurance. Penetration rates are unchanged from 2011 and generally lower than in comparator countries, especially in non-life. Although traditional sale channels continue to predominate, there is increasing diversity in distribution. Risks in life insurance are relatively well spread and in non-life are mainly short-term.